Chloroform-softened gutta-percha with zoe sealer and gutta-percha with zoe sealer mixed with chloroform against standard gutta-percha with zoe sealer A comparative study - Arellano, Ma. Victoria A.
This study compared the effect on apical seals between two ways of using chloroform in obturation against the standard gutta-percha with ZOE sealer technique. Measurement of apical leakage patterns revealed that chloroform-softened gutta percha with ZOE sealer produced the least mean apical leakage followed by the standard gutta-percha with ZOE sealer. Gutta percha with ZOE sealer mixed with chloroform produced the greatest mean apical leakage value.